L’anxiété technocratique en France : les romans du Fleuve Noir « Anticipation », 1951-1960 - Bradford Lyau (ReS Futurae)
Following World War II, France embarked on a process of modernization designed to restore its place as a first-class power. The novels original to Fleuve Noir’s "Collection Anticipation" for the years 1951-60 - and there were hundreds of them - reflect a diversity of attitudes towards this unprecedented technocratic revolution. Among the 1I French authors who wrote books for this series, only two offer visions pretty much wholeheartedly approving of technocracy. Inspired by Saint-Simon and under the pseudonym of F. Richard-Bessière, François Richard and Henri Bessières represent the technocratic order as an ideal paradigm. Four other Fleuve Noir authors largely accept Richard-Bessière’s assumptions, but dissent from them in regard to specifics. M.A. Rayjean questions technocratic priorities ; and Stefan Wul would put a De Gaulle-like leader above the managerial elite and revolorize traditional ways of thinking. Kurt Steiner and Jimmy Guieu, meanwhile, emphasize the biological side of an evolution towards technocracy. Their visions somewhat resemble certain of Olaf Stapledon’s or J.D. Bernal’s (though in Guieu’s case, an ambivalence attaches to the futuristic picture of scientists disincorporating the brains of other human beings to preserve the species). A third group more or less adamantly opposes technocracy or some of its consequences. Kemmel doubts the wisdom of a scientific elite in matters of practical decision-making ; Maurice Limat takes a traditional religious stand against technocracy’s philosophical basis ; Jean-Gaston Vandel and B.R. Bruss have problems with the inequality and oppressiveness of any technocratic scheme of things ; and Peter Randa suggests that virtually any form of social organization is inimical to the radical kind of individualism that he favors. Finally, in a class by himself and counterpointing Richard-Bessière, we have Gérard Klein. The one book he wrote for « Anticipation » during the period covered at first reads like an apology for technocratism. But careful examination suggests that Les chirurgiens d’une planète may well be a deliberate parody of such a rationale. Furthermore, Klein’s novel is perhaps also satirizing the Fleuve Noir formula itself, implying that the demands and expectations of the « Anticipation » series preclude any vision truly alternative to a technocratic one. (Abstract by Robert M. Philmus)